1978
DOI: 10.1530/jrf.0.0530323
|View full text |Cite
|
Sign up to set email alerts
|

Oestrous and ovarian responses to exogenous progesterone and oestrogen in prepubertal ewe lambs in relation to the fecundity of their dams

Abstract: Oestrus was consistently induced by 20, 40 or 80 microgram oestradiol benzoate in progesterone-primed lambs aged 23 weeks and 17 weeks respectively in two experiments. The duration of oestrus increased linearly with increasing log dose of oestrogen, and was negatively correlated with the time of its onset. In the absence of progesterone there was a reduced incidence, later onset and shorter duration of oestrus. Progesterone alone did not induce oestrus. In lambs treated during January (Exp. 2), a later date of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Similar to these results, it has been reported that the incidence of silent ovulations is also greater in lambs than in mature ewes during the normal onset of the breeding season (Quirke, 1981). It has been proposed that the sensitivity of the hypothalamus-pituitary axis to the increase of estrogens may be lower in lambs that in mature ewes (Whyman, 1978). This lower sensitivity may also explain the delay in oestrous onset in yearling ewes.…”
Section: Discussionsupporting
confidence: 81%
“…Similar to these results, it has been reported that the incidence of silent ovulations is also greater in lambs than in mature ewes during the normal onset of the breeding season (Quirke, 1981). It has been proposed that the sensitivity of the hypothalamus-pituitary axis to the increase of estrogens may be lower in lambs that in mature ewes (Whyman, 1978). This lower sensitivity may also explain the delay in oestrous onset in yearling ewes.…”
Section: Discussionsupporting
confidence: 81%
“…This study confirms previous observations (Whyman 1978) that oestrus can be induced by a small dosage of oestrogen in progesterone-primed prepubertal lambs. In the present trial the induced oestrus had commenced in half of the lambs 27 h after injection at 23 weeks of age.…”
Section: Discussionsupporting
confidence: 93%
“…Simplification of the treatment by omitting progesterone priming may lead to a practical testing procedure. Oestrus can be induced in lambs without progesterone priming, although a higher dosage of oestrogen is required to compensate for its absence (Whyman 1978). Further study is needed to establish whether this simpler treatment schedule will produce a response related quantitatively to subsequent ewe fertility in flocks differing in fertility genotype, and to obtain estimates of genetic parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations